2011
DOI: 10.4310/atmp.2011.v15.n6.a7
|View full text |Cite
|
Sign up to set email alerts
|

Codes and supersymmetry in one dimension

Abstract: Adinkras are diagrams that describe many useful supermultiplets in D = 1 dimensions. We show that the topology of the Adinkra is uniquely determined by a doubly even code. Conversely, every doubly even code produces a possible topology of an Adinkra. A computation of doubly even codes results in an enumeration of these Adinkra topologies up to N = 28, and for minimal supermultiplets, up to N = 32.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
188
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(190 citation statements)
references
References 35 publications
0
188
0
Order By: Relevance
“…In this spirit, the authors of [9][10][11][12][13][14][15] developed a detailed classification of a huge class (∼ 10 12 for no more than 32 supersymmetries) of worldline supermultiplets wherein each supercharge maps each component field to precisely one other component field or its derivative, and which are faithfully represented by graphs called Adinkras; see also [16][17][18][19][20][21][22]. The subsequently intended dimensional extension has been addressed recently [7,8], and the purpose of the present note is to complement this effort and identify an easily verifiable obstruction to dimensional extension.…”
Section: Introduction Results and Summarymentioning
confidence: 99%
See 3 more Smart Citations
“…In this spirit, the authors of [9][10][11][12][13][14][15] developed a detailed classification of a huge class (∼ 10 12 for no more than 32 supersymmetries) of worldline supermultiplets wherein each supercharge maps each component field to precisely one other component field or its derivative, and which are faithfully represented by graphs called Adinkras; see also [16][17][18][19][20][21][22]. The subsequently intended dimensional extension has been addressed recently [7,8], and the purpose of the present note is to complement this effort and identify an easily verifiable obstruction to dimensional extension.…”
Section: Introduction Results and Summarymentioning
confidence: 99%
“…In particular, the combinatorial explosion of worldline supermultiplets [12][13][14][15] owes also to the fact that replacing a worldline field with its derivative, φ → . φ = (∂ τ φ), changes only the engineering dimension of the field and produces only minor, though important changes in the supersymmetry relations [42].…”
Section: Adinkramentioning
confidence: 99%
See 2 more Smart Citations
“…The adinkras are being used in order to generate a set of adjacency matrices associated with them which provide the various representations of suppersymmetry. These adjacency matrices satisfy a set of algebraic relations called "Garden Algebra" [26][27][28][29]. In [24] it was shown that one can use the Garden algebra in order to find off-shell completions of supersymmetric theories, by generating a system of quadratic equations.…”
Section: Jhep11(2017)063mentioning
confidence: 99%